2015
DOI: 10.3329/bjp.v11i1.23906
|View full text |Cite
|
Sign up to set email alerts
|

The wound healing effect of <i>Iris forentina</i> on full thickness excisional skin wounds: A histomorphometrical study

Abstract: Iris florentina is an ancient herbal remedy which was prescribed by many physicians due to its positive effects on dermatological problems, specifically skin wounds. Hence, we aimed to investigate the effects of this agent on fullthickness excisional skin wounds in laboratory rats. Three groups of rats (180 ± 20 g; n=8) with 1 cm diameter full-thickness excisional skin wound received daily treatment with I. florentina 10% ointment, and a group with no treatment. By using histomorphometrical methods, the amount… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 18 publications
0
10
0
1
Order By: Relevance
“…On day 0, all the rats were anesthetized with an intramuscular injection of 20 mg/kg ketamine 10% (Merck, Germany) and 2 mg/kg xylazine 2% (Merck, Germany). Then, after the disinfection of the skin of dorsal surface of their neck by betadine 10% (Behvazan pharmaceutical Co. Iran) and shaving the hair, a full-thickness circular excisional skin wound was created with 1 cm diameter on the dorsal surface of the neck by a sterile scissor 21 , 22 .…”
Section: Methodsmentioning
confidence: 99%
“…On day 0, all the rats were anesthetized with an intramuscular injection of 20 mg/kg ketamine 10% (Merck, Germany) and 2 mg/kg xylazine 2% (Merck, Germany). Then, after the disinfection of the skin of dorsal surface of their neck by betadine 10% (Behvazan pharmaceutical Co. Iran) and shaving the hair, a full-thickness circular excisional skin wound was created with 1 cm diameter on the dorsal surface of the neck by a sterile scissor 21 , 22 .…”
Section: Methodsmentioning
confidence: 99%
“…Finally, in a regular procedure, increasing skin strength is performing and results in healing of the injured tissues. 2 It has been proven that many herbal extracts accelerate the wound healing process through angiogenesis, 6,7 activation of NF-kB, 8 proinflammatory cytokines, 9 iNOS, 10 collagen alpha1 type I upregulation, 11 the proliferation of fibroblasts, 12 and antioxidant activity. 9 In recent years, the concentration of researchers on complementary and herbal medicine has increased throughout the world.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that about 1/3rd of all herbal medicines in use are for the treatment of skin disorders and wounds (Mantle et al, 2001). Various plants such as Allium sativum (Farahpour et al, 2017), Aloe vera (Maenthaisong et al, 2007), Carica papaya (Gurung and Skalko-Basnet et al, 2009), Centaurea pterocaula (Ötün and Yücel, 2019), Iris forentina (Mirmalek et al, 2015), Otostegia persica (Ganjali et al, 2013), Pistacia lentiscus (Djerrou et al, 2010) have been investigated for the treatment of burn.…”
Section: Introductionmentioning
confidence: 99%